Current Situation and Prospects of Regional Development in Mongolia: On the Example of the Eastern Region - Dashnyam, Sarangerel; Gungaa, Baljinnyam (The journal of contemporary issues in business and government, 2021)
The concentration of population, production and services in Ulaanbaatar, the capital city of Mongolia, has led to increasing economic inequality in the capital city and regional and rural areas and widening urban-rural disparitiesalthough thecountry’s economy has been growing in recent years. 46 percent of the total population of the country (1,463,000) and 64.2 percent (50,467)of the active business entities and organizations [1] are concentrated in the capital city. Stimulating the local economy and ensuring sustainable growth in the medium and long termis necessary to reduce this concentration and development disparity. Therefore, it is crucial to analyze the needs and develop regional development policies and strategies.As the regional development policy is the primary policy to implement all Mongolia's sustainable development policies at the local level, regional and provincial development issues are significant.Mongolian regional development level is measured by regional economic growth, inflation, budget, investment, and key indicators of certain sectors of the economy such as population, density, births, deaths, migration, unemployment, poverty and human development index.